2015
DOI: 10.1302/0301-620x.97b3.34791
|View full text |Cite
|
Sign up to set email alerts
|

Sliding hip screw versus sliding helical blade for intertrochanteric fractures

Abstract: The spiral blade modification of the Dynamic Hip Screw (DHS) was designed for superior biomechanical fixation in the osteoporotic femoral head. Our objective was to compare clinical outcomes and in particular the incidence of loss of fixation. In a series of 197 consecutive patients over the age of 50 years treated with DHS-blades (blades) and 242 patients treated with conventional DHS (screw) for AO/OTA 31.A1 or A2 intertrochanteric fractures were identified from a prospectively compiled database in a level 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…Of these factors, good fracture reduction appears to be of paramount importance. This is logical because doing so also effectively restores maximal contact of any available bony buttress [ 15 , 21 , 22 ]. For a dynamic device to work without excessive collapse, a majority of bone along the femur's circumference should remain intact and in contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these factors, good fracture reduction appears to be of paramount importance. This is logical because doing so also effectively restores maximal contact of any available bony buttress [ 15 , 21 , 22 ]. For a dynamic device to work without excessive collapse, a majority of bone along the femur's circumference should remain intact and in contact.…”
Section: Discussionmentioning
confidence: 99%
“…Our objective was to test the hypothesis on whether patients with increasing degree of fracture collapse and shortening after DHS had impaired walking and increased incidence of adverse events. We carried out a secondary analysis of a consecutive prospective cohort of patients with trochanteric fractures treated with two similar DHS designs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The helical blade received regulatory approval in 2005 and was designed to provide stronger fixation through impaction of the cancellous bone which should increase resistance to cut-out67). However, several randomized controlled trials comparing helical blade with the lag screw in intramedullary fixations have demonstrated greatly different outcomes compared with published data and theoretical concepts789101112).…”
Section: Introductionmentioning
confidence: 99%
“…Data for TAD and cut-out complication were reported in five studies involving femoral intertrochanteric fractures treated with CHS in supine position with a traction table ( Table 4 ). They were compared with this study 22 23 24 25 26) and the results were superior for patients with femoral intertrochanteric fractures treated in the lateral decubitus position. Adequate TAD means accurate screw position associated with less cut-out failure 25) .…”
Section: Discussionmentioning
confidence: 96%